2004
DOI: 10.1021/nl0497272
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Carbon Nanoscrolls

Abstract: Carbon nanotube scrolls (CNSs) provide an interesting form of carbon that ideally consists of a single sheet of graphite that is spiral wrapped to form a nanotube. We here use molecular dynamics simulations to investigate CNS formation, stability, and the structural effects due to charge injection. CNS formation is seen to automatically occur when a critical overlap between sheet layers is achieved for the partially curled sheet. We find that charge injection causes unwinding of the CNSs, which might be import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
328
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(352 citation statements)
references
References 18 publications
19
328
1
4
Order By: Relevance
“…5c shows that the progress of rolling energy for the pure carbon graphene sheet (rGOx-NS, black line) is not linear and initially increases, but as soon as the graphene layers start to interact, the rolling energy decreases because of the mutual interlayer interaction. This trend is in agreement with a study by Braga et al 14 More interestingly, when nitrogen defects are incorporated in the graphene lattice, and a maghemite, Fe 20 O 32 Fig. 5d) lowers the formation energy further, supporting our experimental observations that a high loading seems essential for an efficient rolling.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…5c shows that the progress of rolling energy for the pure carbon graphene sheet (rGOx-NS, black line) is not linear and initially increases, but as soon as the graphene layers start to interact, the rolling energy decreases because of the mutual interlayer interaction. This trend is in agreement with a study by Braga et al 14 More interestingly, when nitrogen defects are incorporated in the graphene lattice, and a maghemite, Fe 20 O 32 Fig. 5d) lowers the formation energy further, supporting our experimental observations that a high loading seems essential for an efficient rolling.…”
Section: Resultssupporting
confidence: 93%
“…Similarly, control experiments with low-level or non-N-rGOx decorated by maghemite particles show no rolling, indicating that the nitrogen defects are largely involved in the rolling mechanism. Different to earlier reports 18 and to theoretical predictions 14 , we show that the rolling process is fully reversible and that the N-rGOx can be fully transformed back to open graphene sheets by the removal of iron oxide particles through acid washing. We conclude that the rolling is initiated by the strong adsorption of maghemite nanoparticles at nitrogen defects in the graphene lattice and their mutual magnetic interaction.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…We carried out molecular dynamics simulations in the framework of classical mechanics with standard force field [22], which includes van der Waals, bond stretch, bond angle bend, and torsional rotation terms. This methodology has been proven to be very effective for the study of dynamical properties of complex structures [23,24,25,26]. For all simulations the following convergence criteria were applied: maximum force of 0.005 kcal/mol/Å, root mean square (RMS) deviations of 0.001 kcal/mol/Å, energy differences of 0.0001 kcal/mol, maximum atomic displacement of 0.000 05Å, and RMS displacement of 0.000 01Å.…”
mentioning
confidence: 99%
“…CNS was first reported as a new material for hydrogen storage in 2003 [199]. Braga et al [200,201] showed by molecular dynamic simulations that hydrogen can be adsorbed at 77 K but no significant adsorption takes place at 300 K. The stored hydrogen can be desorbed by increasing the temperature to about 400 K. These nanoscrolls had internal diameter of 2 nm and interlayer distance of 0.34 nm. In one of their very recent computational studies on CNS, Mpourmpakis et al [202] reported that pure CNS could not accumulate hydrogen because the interlayer distance was very small.…”
Section: Carbon and Carbon-based Nanostructuresmentioning
confidence: 99%